The theory of chronic stress as a scientific model in Cognitive Neuroscience - Moscoso, Manolete (2015)
The scientific study of stress presents serious conceptual and methodological limitations. The theory and concepts of allostasis and allostasis load allowed a new integrative framework of the concept of chronic stress, that identifies the brain as the mediator of the interactions among the central nervous system and immune system in the development of disease. We examined the negative impact of chronic stress and the perceived emotional distress on illness. Our research on the Mindfulness Based Stress Reduction (MBSR) serves as an illustration of psychological and neurobiological outcomes; and how this therapeutic approach facilitates the reduction of perceived emotional distress in cancer patients and their caregivers.